Opportunities and challenges to advance the use of electronic patient-reported outcomes in clinical care: a report from AMIA workshop proceedings. Issue 4 (20th August 2019) - Austin, Elizabeth; LeRouge, Cynthia; Hartzler, Andrea L; Chung, Arlene E; Segal, Courtney; Lavallee, Danielle C
Abstract: Despite the demonstrated value of patient-centered care, health systems have been slow to integrate the patient's voice into care delivery through patient-reported outcomes (PROs) with electronic tools. This is due in part to the complex interplay of technology, workflow, and human factors that shape the success of electronic PROs (ePROs) use. The 2018 American Medical Informatics Association Annual Symposium served as the setting for a half-day interactive workshop with diverse stakeholders to discuss proposed best practices for the planning, design, deployment, and evaluation of ePROs. We provide this collective commentary that synthesizes participant feedback regarding critical challenges that prohibit the scale and spread of ePROs across healthcare delivery systems, including governance and leadership, workflow and human factors, informatics, and data science. In order to realize the promise of ePROs at scale, adaptable approaches are critical to balance the needs of individual users with health systems at large.